PMP: Pemberdayaan Kelompok Remaja Masjid Al-Karomah dalam Pembuatan Virgin Coconut Oil wangi Pandanus Amarylifolius (VCO wangi daun pandan) untuk kesehatan kulit lanjut usia di Kecamatan Tenayan Raya - Ovari, Isna; Winda, Desy; Fikha, Iqra Idri; Wahyuni, Fitra (Journal Of Human And Education (JAHE), 2024)
The empowerment activities for the Al-Karomah Mosque youth group in Bencah Lesung Village, Tenayan Raya Subdistrict, are a Community Service Program between STIKes Pekanbaru Medical Center and the target partner, the Al-Karomah Mosque youth. The activities include the following sequence: first, the target partner is provided with knowledge about Virgin Coconut Oil (VCO) with the fragrance of Pandanus Amaryllifolius. Next, the mosque youth are trained and guided directly in making Virgin Coconut Oil with the fragrance of Pandanus Amaryllifolius (VCO with pandan leaf fragrance). After that, the VCO is packaged into glass bottles and labeled. Subsequently, the elderly members of the Al-Karomah Mosque congregation (who are members of the Majelis Taklim) are gathered for a health counseling session on the use of VCO with pandan leaf fragrance for elderly skincare. This community service activity has been carried out at the Al-Karomah Mosque. The VCO with pandan leaf fragrance produced from this activity has been well-received by the elderly, as it has numerous benefits for the skin, including the distinctive pandan leaf fragrance, the clarity of the oil, its safety from chemicals, ease of use, the attractive bottle design, and, importantly, its affordability. The outcomes of this activity are as follows: based on data analysis, the Al-Karomah Mosque youth group has increased their knowledge about VCO with pandan leaf fragrance, including its production, packaging, and usage for the elderly. After receiving training and direct practice in making VCO with pandan leaf fragrance, the mosque youth are now able to produce it simply. Evaluation from the elderly who have been using the VCO regularly for 4 weeks indicates noticeable changes in their skin, such as feeling softer, smoother, and more hydrated. The sequence of these activities can be viewed in videos uploaded on Instagram, YouTube, and TikTok by STIKes Pekanbaru Medical Center. The news of this activity has also been featured in the Pekanbaru Pos electronic print media. And will also be published in the Journal of Human and Education (JAHE), which has been accredited by SINTA 5.